In-vitro Prevention of Cataract by Ginseng on Isolated Goat Eye Lens - S, Nithya; S, Sumadhuri; J, Anbu; M, Sumithra (Pharmacognosy Communications)
Objective: The aim of the present work was to evaluate the in vitro effect of ginseng on cataract induced by glucose. Materials and Methods: Goat eye lenses were divided into four groups. Group I lenses were incubated in artificial aqueous humor with glucose concentration 5.5 mM (normal control). Group II lenses were incubated with glucose concentration 55 mM (toxic control). Group III and IV lenses incubated with glucose concentration 55 mM were incubated along with ginseng 50 and 100mg/ml and subjected to morphological and biochemical evaluation. Results: Group II lenses showed high amounts of malondialdehyde (MDA) soluble and insoluble protein and decreased catalase and glutathione levels., Lenses treated with ginseng showed significant (P < 0.05) reductions in MDA, as well as increased levels of catalase (P < 0.001), glutathione (P < 0.005) and total and soluble protein. Conclusions: Ginseng showed prevention of in vitro glucose induced cataract. Thus the goat lens model could be used for testing of various anticataract agents.
Keywords: Cataract; catalase; in vitro; glutathione; lens; ginseng; Panax ginseng